Correlation Analysis of Interpersonal Communication Competence of Corporate Social Responsibility Facilitators, Stakeholder Trust Level, and Corporate Reputation - Retno Wulandari; Agus Naryoso; Arifa Rachma Febriyani; Siti Ahmaniyar (CHANNEL: Jurnal Komunikasi, 2021)
The problem of communication such as misunderstanding, there is no feedback, and the ineffectiveness of a message often occurs while the company communicates or interacts with stakeholders, moreover runs the CSR program. The communication problems above affected one of the CSR goals. CSR can improve people living in the region around the company like happened in the District of North Semarang because it has the highest poverty rate in Semarang city. Not achieving the CSR objectives will because residents who live around the company have poor judgments against the company and have no trust against the company and so, causes a poor reputation against the company. Moreover, if the company has excessive gas emission and one of them is PT. Indonesia Power Semarang PGU. The research has the purpose of determining if there is a relationship between the effectiveness of interpersonal communication done by the facilitator of CSR and the level of trust beneficiaries with the reputation company of PT. Indonesia Power Semarang PGU. This research is a quantitative research using the theory of communication effectiveness and reasoned action (TRA). Sample this research is Group guidance of PT. Indonesia Power Semarang PGU is the Joint Business Group (KUB) Prima Indosutera in the District of North Semarang. Based on the research results, the effectiveness of interpersonal communication and trust beneficiariesâ€™ level significantly relates to its reputation. The things above showed through the significance value of the hypothesis test performed, more effectively the communication interpersonal has done so. The companyâ€™s reputation is better (positive) than such a hypothesis has a significance value of 0.000 (0.000 s of 0.01).Â